Intestinal Stem Cell Niche Insights Gathered from Both In Vivo and Novel In Vitro Models - Nikolce Gjorevski; Paloma Ordóñez-Morán (Hindawi Limited, 2017)
Intestinal stem cells are located at the base of the crypts and are surrounded by a complex structure called niche. This environment is composed mainly of epithelial cells and stroma which provides signals that govern cell maintenance, proliferation, and differentiation. Understanding how the niche regulates stem cell fate by controlling developmental signaling pathways will help us to define how stem cells choose between self-renewal and differentiation and how they maintain their undifferentiated state. Tractable in vitro assay systems, which reflect the complexity of the in vivo situation but provide higher level of control, would likely be crucial in identifying new players and mechanisms controlling stem cell function. Knowledge of the intestinal stem cell niche gathered from both in vivo and novel in vitro models may help us improve therapies for tumorigenesis and intestinal damage and make autologous intestinal transplants a feasible clinical practice.